Attentional and interpretive bias towards illness‐related information in chronic fatigue syndrome: A systematic review. Issue 4 (6th October 2016) - Hughes, Alicia; Hirsch, Colette; Chalder, Trudie; Moss‐Morris, Rona
Abstract : Purpose: Chronic fatigue syndrome (CFS) is characterized by severe and debilitating fatigue. Studies based on self‐report measures suggest negative illness representations, related symptom interpretations, and heightened symptom focusing are maintaining factors of fatigue. This study reviews studies which have investigated these cognitive biases using experimental methods, to (1) review the evidence for information processing biases in CFS; (2) determine the nature of these biases, that is the stages cognitive biases occur and for what type of stimuli; and (3) provide directions for future methodologies in this area. Methods: Studies were included that measured attention and interpretation bias towards negative and illness‐related information in people with CFS and in a comparison group of healthy controls. PubMed, Ovid, CINAHL, PsycINFO, Web of Science, and EThOS were searched until December 2014. Results: The evidence for cognitive biases was dependent on the methodology employed as well as the type and duration of the stimuli presented. Modified Stroop studies found weak evidence of an attentional bias in CFS populations, whereas visual‐probe studies consistently found an attentional bias in CFS groups for health‐threatening information presented for 500 ms or longer. Interpretative bias studies which required elaborative processing, as opposed to a spontaneous response, found an illness‐related interpretive bias in the CFS group compared to controls. Conclusions: Some people with CFS have biases in the way they attend to and interpret somatic information. Such cognitive processing biases may maintain illness beliefs and symptoms in people with CFS. This review highlights methodological issues in experimental design and makes recommendations to aid future research to forge a consistent approach in cognitive processing research. Statement of contribution What is already known on this subject? Studies based on self‐report measures suggest negative illness representations, related symptom interpretations, and heightened symptom focusing contribute to the maintenance of chronic fatigue. Experimental studies in other clinical populations, such as patients with anxiety, depression, and chronic pain, have identified illness‐specific biases in how information is implicitly attended to and interpreted, which has a causal role in these conditions. What does this study add? This is the first review of implicit cognitive processes in chronic fatigue syndrome (CFS). Sustained attention and negative interpretations of somatic information may reinforce negative illness beliefs. Cognitive processes have a role to play in the cognitive behavioural model of CFS.